Moderate water stress does not inhibit nitrogen remobilization, allowing fast growth in high nitrogen content Quercus variabilis seedlings under dry conditions. (14th December 2018) - Wang, Jiaxi; Villar-Salvador, Pedro; Li, Guolei; Liu, Yong
Abstract: Remobilization of stored nitrogen (N) plays an important role in the early growth of deciduous trees in spring. Several environmental factors can modulate N remobilization, but whether water stress is one such factors is unknown. This study analyzes how the size of N storage in Quercus variabilis Blume seedlings interacts with water stress to affect N remobilization, uptake and new growth. This information is important for improving success of forest tree plantations under dry spring conditions. During the first growing season, we produced seedlings with distinct N content by applying two fall N fertilization rates (12 or 24 mg N per seedling) using 15 N-enriched fertilizer. At the beginning of the second growing season, a new experiment was started where seedlings were transplanted into larger pots and subjected to two watering levels (85 or 40% of field capacity). The plants were sampled at 4 weeks (T1 ), 8 weeks (T2 ) and 12 weeks (T3 ) after transplanting. Low watering reduced the growth of high and low N seedlings, but high N seedlings showed greater growth than low N seedlings. During bud burst and initial shoot elongation (T1 ), restricted watering, which induced a moderate water stress, did not affect the amount of N remobilized from roots, the major source of stored N source at this growth stage. This suggests that high N storage can partially counteract the negative effect of moderate water stress on early growth. At T1, water stress did not affect N uptake, and high N content seedlings absorbed significantly less soil N than did low N content seedlings. At T3, in contrast, water stress was the main determinant for N uptake, with drought-stressed plants showing lower uptake than well-watered plants. We conclude that moderate drought does not inhibit N remobilization from the major storage organ at early growth stages in spring, and that increasing N storage of planted seedlings through fall fertilization can mitigate the negative effect of moderate spring drought on growth.